Outcomes of linezolid, glycopeptides, and other regimens in ampicillin-resistant, vancomycin-susceptible and vancomycin-resistant enterococcal bacteremia in a resource-limited setting: stewardship implications - Yameena Noman Khan; Ali Mala; Rubab Murtaza; Irshad Batool; Azizullah Khan; Imtiaz Begum; Jamil Muqtadir; Abdul Rasheed; Sameeullah Bhatti (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Enterococcal bloodstream infections (BSI) are associated with high morbidity and limited treatment options, particularly in resource-limited settings where access to standard agents may be constrained. Comparative effectiveness data directly informing the choice among available agents for both vancomycin-resistant (VRE) and ampicillin-resistant, vancomycin-susceptible (VSE) enterococcal bacteremia are specifically lacking in such settings, where regimen selection is frequently dictated by drug availability and cost rather than guideline preference. We conducted a retrospective cohort study across three hospitals of a single university health system (Dr. Ziauddin University, Karachi, Pakistan) including hospitalized adults (≥ 18 years) with clinically significant enterococcal bacteremia (a positive blood culture together with clinical evidence of infection, as adjudicated by the treating physician) between January 1, 2010, and May 31, 2025. Only the first episode per patient was analyzed. VRE and VSE cohorts were compared for baseline characteristics and empiric therapy. Definitive monotherapy—receipt of a single study agent active against the isolate, assigned within the prespecified 48- to 72-h window after index blood culture (time-zero), by which time organism identification and susceptibility results were generally available—was assessed within the VRE and VSE cohorts. Because discharge alive is a competing event for in-hospital death, cumulative incidence functions (CIF) with Gray’s test and an adjusted Fine–Gray competing-risks model (adjusted for age, Charlson Comorbidity Index, qPitt score, septic shock, and definitive antibiotic exposure (vancomycin, teicoplanin, daptomycin, tigecycline)) were used. Of 925 screened patients, 501 met inclusion criteria (VSE n = 404; VRE n = 97). VRE bacteremia presented with greater acute severity (higher APACHE II) and was more frequently catheter-associated, while VSE more often had urinary and intra-abdominal sources (all p < 0.001). In definitive monotherapy analyses among VRE ( n = 67; tigecycline excluded, as it was used only as salvage therapy), 28-day mortality was numerically higher with teicoplanin (66.7%) but did not differ significantly across linezolid, teicoplanin, and daptomycin; CIF analysis similarly showed no difference in cumulative incidence of in-hospital death (Gray’s p = 0.246). Tigecycline, used only as salvage therapy, was associated with higher 28-day mortality (80.0% vs 47.8%; p = 0.003; Supplementary Table S1). In VSE monotherapy ( n = 404), teicoplanin exposure was associated with higher ICU admission and higher 28-day mortality, and CIF curves differed across vancomycin, teicoplanin, and linezolid (Gray’s p < 0.001); however, the linezolid-exposed group had sparse/zero events for several endpoints, suggesting confounding by indication. In the adjusted Fine–Gray model, higher qPitt score was independently associated with mortality (sHR 2.21, 95% CI 1.62–3.01; p < 0.001). Tigecycline (sHR 4.00, 95% CI 2.11–7.60; p < 0.001) and daptomycin exposure (sHR 3.11, 95% CI 1.37–7.07; p = 0.007) were associated with higher subdistribution hazard of death, whereas vancomycin exposure was associated with lower hazard (sHR 0.36, 95% CI 0.20–0.67; p = 0.001). In this multi-hospital, single-system cohort, VRE bacteremia was more severe and more often catheter-associated than VSE. When accounting for discharge as a competing event, mortality differences across definitive monotherapy groups were not significant in VRE, while VSE comparisons were influenced by treatment selection and sparse outcome counts in some groups. Severity (qPitt score) was a key independent predictor of mortality, and observed antibiotic–mortality associations should be interpreted cautiously given confounding by indication.